Wealth, water and wildlife: Landscape aridity intensifies the urban luxury effect. Issue 9 (9th June 2020) - Chamberlain, Dan; Reynolds, Chevonne; Amar, Arjun; Henry, Dominic; Caprio, Enrico; Batáry, Péter
Abstract: Aim: Urban biodiversity, and its associated ecosystem services, is an important component of the quality of life of urban residents. The "luxury effect" posits a positive association between biodiversity and socioeconomic status in urban areas, and is thus reflective of environmental injustice, as the benefits associated with biodiversity are not equitably shared across society. We aimed to determine the generality of the luxury effect, and to identify the factors causing its variation across published studies. Location: Urbanized landscapes globally. Time period: Current. Major taxa studied: Terrestrial animals and plants. Methods: We tested the luxury effect across a sample of 337 estimates of the relationship between biodiversity measures and socioeconomic status from 96 studies via a meta‐analysis, addressing three hypotheses: (a) the luxury effect is more pronounced where water availability is limited, (b) the luxury effect is more pronounced in developing than developed countries, (c) the luxury effect is stronger in exotic compared to native species. Results: There was a significant overall luxury effect: there was a positive association between terrestrial biodiversity measures and socioeconomic status. The strength of the luxury effect was greater in arid areas. There was limited support for a stronger luxury effect in exotic species, but no support for any association with development status. Main conclusions: Many key and emerging climate impacts are concentrated in urban areas. Therefore, the degree of environmental injustice represented by the luxury effect may be amplified in the future, especially in arid regions. The objective to increase urban biodiversity through more equitable management and provision of water resources could form part of a wider strategy for sustainable development of cities to promote environmental justice, enhancing the quality of life of urban residents across all sectors of society. Challenges remain to ensure that any such strategy prioritizes conservation goals for native biodiversity.